Implementação da BNCC nas escolas públicas em Humaitá (AM): uma análise da percepção dos professores de língua inglesa - Oliveira, Leilane Souza (Brasil, 2025)
This article seeks to analyze the implementation process of the National Common Curricular Base (in Portuguese - BNCC) in elementary schools in Humaitá (AM) from the perspective of English language teachers. We now realize the challenges of this process of adaptation to implementation, after six years since BNCC's regulatory and guiding changes. The research is a qualitative approach, for which the following instruments were used: a) form for English language teachers, in order to generate data and establish the profile of research participants; b) interview in order to give participants a voice about the implementation of the BNCC. The basis of the research is based on reading official documents and others that can help reflect on the BNCC's path so far, namely: Brasil (2018), Cruz e Castro (2019), Byram and Hu (2013), Kachru (1991), among others. As a result, we observed that the implementation of the BNCC shows that research participants have a critical view of the document, confirm its potential and seek to simplify it to the municipal context in which they are inserted, however, there are implications such as: the resources and infrastructure that distance them from the document, in addition to the lack of ongoing training.